Preparation and characterization of tissue-factor-loaded alginate: Toward a bioactive hemostatic material. (1st December 2020) - Liu, Chengkun; Shi, Zhuang; Sun, Haiyan; Mujuni, Christopher J.; Zhao, Lili; Wang, Xiaoqiang; Huang, Fang
Highlights: Tissue factor (TF) embedded in alginate is developed into a hemostatic material. Alginate concentration or cross-linking can regulate TF release. The combination with alginate enhances TF procoagulant activity. TF-in-alginate shows a great hemostatic property inducing quick blood clotting. TF-in-alginate exhibits no cytotoxicity against mammalian cells. Abstract: Tissue factor (TF), an integral membrane protein, is by far the most potent known triggering agent of blood coagulation. Inspired by TF's effectiveness in initiating coagulation, this work aims to develop hemostatic materials with TF-integrated liposomes, which combined with alginate biopolymers are designed as composite pastes or hydrogels cross-linked with Ca 2+ . Fluorescence measurements revealed that the proteoliposomes were evenly distributed within alginate matrices, which also remained intact after release into simulated body fluid. The proteoliposome release rate from the composite pastes increased with the decrease of alginate concentration from 3% to 1%, or relative to the corresponding hydrogels. The latter also showed a swelling property. The combination with alginate enhanced TF procoagulant activity, and most importantly the resultant composites exhibited superior hemostatic performance, yielding a shortest blood clotting time of 1.5 min while untreated blood took 14.2 min to clot, with no cytotoxicity against mammalian cells.